Formulation of Graphene Nanoplatelets Nanofluid As Heat Transfer Fluid On Photovoltaic-Thermal System Analysis - Muhamed Rafaizul, Nurul Izzati Akmal (2024)
Photovoltaic-thermal (PV/T) systems have gained significant attention as an energy-efficient and sustainable technology. The use of nanofluids as heat transfer fluid in PV/T system has generated a lot of interest in recent years due to their improved thermophysical properties compared to conventional heat transfer fluids. Although researchers’ interest in improving the performance of PV/T systems by using nanofluids as heat transfer fluid has grown over the past years, there is still a lack of studies related to this application. This study investigates the efficiency enhancement of PV/T systems by utilizing graphene nanoplatelets (GNP) nanofluids compared to conventional water-based fluids. This research aims to create a formulation of GNP at concentrations of 0.2, 0.4, 0.6, 0.8 and 1.0 wt.%, determine the physical properties of GNP through FESEM, PSA and XRD analysis and thermophysical properties of the nanofluids through thermal conductivity, viscosity, density and specific heat capacity, and evaluate the overall performance of the PV/T utilizing the best concentration of GNP nanofluid. To formulate the nanofluid, the two-step method is used. The addition of surfactant, polyvinylpyrrolidone (PVP) is done to enhance the stability of the nanofluid and is assessed through direct observation method. The best nanofluid concentration undergoes thermophysical properties test and is utilized in a PV/T system to run an indoor experiment using an indoor solar simulator. Through a comprehensive analysis of thermal and electrical efficiencies at varying flow rates in range of 20 to 80 L/hr, the research aims to evaluate the impact of nanofluid technology on PV/T system performance. The results demonstrate that GNP nanofluids were successfully formulated through the two-step method and exhibit superior thermal conductivity and other heat transfer properties, with the concentration of 0.6 wt.% having the best stability and thermophysical properties tested which are thermal conductivity (0.6611 W/mK), viscosity (1.22 mPa.s), density (476.8 kg/m3) and specific heat capacity (3606.4 J/kgK) leading to enhanced thermal efficiency up to 80% in PV/T systems across all flow rates. Additionally, the electrical efficiency of PV/T systems achieved 8.9% efficiency, highlighting the potential benefits of improved thermal management and heat dissipation. Overall, the study concludes that GNP nanofluids outperform conventional heat transfer fluids in terms of efficiency, with 88.9% and an enhancement of 17% across various flow rates and solar irradiance ranging from 200 to 800 W/m2, emphasizing the significant role of nanofluid technology in advancing the sustainability and effectiveness of solar energy applications. The findings provide valuable insights for optimizing the operation of PV/T systems and pave the way for further research into enhancing the performance of renewable energy systems through nanofluid innovation.